The Effects of Dextran on Postoperative Thrombosis and Hemodilution in Microvascular Head and Neck Reconstruction. Issue 1 (July 2020) - Filipan, Dorotea; Dediol, Emil; Blivajs, Igor; Milic, Morena
Abstract : Background: Free tissue transfer is an integral part of reconstructive head and neck surgery today. Although increased experience and refinements in techniques have minimized flap loss, pharmacological agents have been used to prevent thrombus formation and flap failures, despite their questionable effectiveness. The aim of this study is to investigate the use of dextran 40 in thrombosis prophylaxis, as well as its effects on blood coagulability and flap survival. Methods: This is a retrospective analysis of 176 free flaps performed at University Hospital Dubrava, Zagreb, Croatia, during a 4-year period. A comparison was made between 2 patient groups, based on their respective postoperative prophylaxis protocols. All patients were treated with low-molecular-weight heparin as deep vein thrombosis prevention, until patient mobilization. Group 1 was on dextran 40 protocol, whereas group 2 did not receive additional treatment. Primary outcome of the study was determined as flap loss rate, whereas secondary outcome was evaluated as the rate of thrombosis or hemorrhage. The hemodilution potential of dextran 40 was examined through blood count laboratory values. Results: Total flap survival rate was 90.34%. There were 16 free flap losses and 1 partial loss overall. Anastomoses were re-explored in a total of 27 cases, of which 17 were salvaged. There were 29 events of hemorrhage or arterial or venous thrombosis: 17 in group 1 and 12 in group 2. A sum of 26 incidences of other postoperative complications was recorded, 13 in each group. Hemodilution status showed a statistically significant reduction in erythrocyte count and hemoglobin and hematocrit levels in the group receiving dextran 40, on postoperative days 1 and 3, but no such effect was observed on postoperative platelet count. Conclusions: Although dextran 40 has been shown to have a valuable effect on hemodilution, which is beneficial in microsurgery, it did not demonstrate better outcomes in terms of flap survival. Because it can cause serious systemic complications, it is better not to administer it routinely. However, its important influence on reduction in erythrocyte count and hemoglobin and hematocrit levels should be further investigated.